2018
DOI: 10.1155/2018/4907264
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin for Atypical Antipsychotic-Induced Metabolic Adverse Effects: A Meta-Analysis of Randomized Controlled Trials

Abstract: The objective of our study was to determine the effect of melatonin administration on atypical antipsychotic-induced metabolic adverse effects in patients with psychiatric disorders. A systematic search was performed in PUBMED, Cochrane Library, Scopus, Web of Science, and EBSCOhost electronic databases. Randomized controlled trials studying the effect of melatonin on antipsychotic-induced metabolic adverse effects were identified and subjected to meta-analysis. Four studies were included in the meta-analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
0
10
1
Order By: Relevance
“…Our findings revealed a definite positive role of melatonin agonists on cardiovascular parameters differently from the previous two meta-analyses on the same topic (Igwe & Brigo, 2018;Kamath & Rather, 2018). The meta-analysis conducted by Igwe and Brigo concluded that no statistically significant difference in any anthropometric or metabolic variable emerged in patients treated with melatonin (Igwe & Brigo, 2018).…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…Our findings revealed a definite positive role of melatonin agonists on cardiovascular parameters differently from the previous two meta-analyses on the same topic (Igwe & Brigo, 2018;Kamath & Rather, 2018). The meta-analysis conducted by Igwe and Brigo concluded that no statistically significant difference in any anthropometric or metabolic variable emerged in patients treated with melatonin (Igwe & Brigo, 2018).…”
Section: Discussioncontrasting
confidence: 74%
“…[95% CI, −7.00 to −1.88]; p = 0.0007), but not in the systolic blood pressure (MD = −4.23 [95% CI, −8.11 to −0.36]; Kamath & Rather, 2018). This discrepancy in findings can be explained by several factors.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…143 Another hormone, melatonin, may be therapeutically useful during the menopause to counteract sleep disturbance and, also, as has been shown recently, to prevent metabolic side effects induced by antipsychotic drugs. 144149…”
Section: Other Hormones Potentially Relevant To Postpartum Disorders mentioning
confidence: 99%
“…However, previous systematic reviews and meta-analyses on medications for alleviating AAPs-induced metabolic disturbance were limited to a particular pharmacological intervention (e.g. metformin only, GLP-1RAs only, topiramate only, nizatidine only, ranitidine only, or melatonin only) (De Silva et al, 2016;Gu et al, 2018;Hiluy et al, 2019;Kamath and Rather, 2018;Paravattil et al, 2016;Siskind and Hahn, 2018) and could not provide which intervention is superior in efficacy and tolerability. Compared to standard meta-analysis, network meta-analysis (NMA) allows assessment of efficacy and tolerability of two or more interventions (Cipriani et al, 2013).…”
Section: Efficacy and Tolerability Of Pharmacological Interventions On Metabolic Disturbance Induced By Atypical Antipsychotics In Adultsmentioning
confidence: 99%